2014
DOI: 10.1039/c3gc41377b
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of TiO2crystal structure on the enhanced activity and stability of Ru/TiO2catalysts for the conversion of lignin-derived oxygenates

Abstract: Although Ru catalysts supported on reducible oxides such as TiO 2 hold significant promise for the deoxygenation of biomass derived oxygenates, a significant drawback is their instability under oxidation conditions necessary for catalyst regeneration. In this contribution, the role of TiO 2 crystal structure on resistance to metal particle sintering during calcination treatments at 400 and 500 °C is investigated. The resulting impact of the calcination temperature and TiO 2 support phase for the conversion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
82
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 40 publications
6
82
0
3
Order By: Relevance
“…The state of the art also provides the knowledge to demethoxylate such methoxylated (alkyl)phenols, yielding selectively the alkylphenol at high conversions (and methane or methanol, conversion C). [28][29][30][31][32][33][34][35][36][37][38] The high selectivity to lignin monomers using the ligninfirst strategy stands in great contrast to many other state-ofthe-art depolymerization techniques, such as pyrolysis, 39,40 base-catalyzed depolymerisation, 41,42 and hydrogenolysis. 43,44 The latter works yield, besides often substantial unwanted side products as char and light gases, a wide variety of up to 20 or more products, and a phenol yield limited to ca.…”
Section: Introductionmentioning
confidence: 99%
“…The state of the art also provides the knowledge to demethoxylate such methoxylated (alkyl)phenols, yielding selectively the alkylphenol at high conversions (and methane or methanol, conversion C). [28][29][30][31][32][33][34][35][36][37][38] The high selectivity to lignin monomers using the ligninfirst strategy stands in great contrast to many other state-ofthe-art depolymerization techniques, such as pyrolysis, 39,40 base-catalyzed depolymerisation, 41,42 and hydrogenolysis. 43,44 The latter works yield, besides often substantial unwanted side products as char and light gases, a wide variety of up to 20 or more products, and a phenol yield limited to ca.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Such interfaces can form the basis of bifunctional catalysis,w here each material contributes its unique functionality to the active site.F or example,b ifunctional catalysts have shown promise for selective hydrodeoxygenation (HDO) of alcohols/aldehydes with aromatic substituents,adesirable path for production of fuels or chemicals from biomass ( Figure 1a). [4][5][6][7][8] Thei mportance of interfacial sites in catalysis suggests that catalyst design should emphasize novel methods for tailoring these interfaces that go beyond using the oxide as as imple catalyst carrier. [4][5][6][7][8] Thei mportance of interfacial sites in catalysis suggests that catalyst design should emphasize novel methods for tailoring these interfaces that go beyond using the oxide as as imple catalyst carrier.…”
mentioning
confidence: 99%
“…Besides the effect of basicity or acidity of the support, the effect of the crystal structure of the support should also be considered. Omotoso and co‐workers have found that the TiO 2 crystal structure affects the activity and stability of Ru/TiO 2 catalysts for the conversion of guaiacol at 400 °C and atmospheric pressure of H 2 . The rutile phase but not the anatase phase plays an important role in stabilizing the Ru particles during calcination pretreatment.…”
Section: Upgrading Lignin Pyrolysis Vapors By Hydrodeoxygenationmentioning
confidence: 99%